Impact of rainfall to the effectiveness of pig slurry shallow injection method for NH3 mitigation in a Mediterranean soil. (1st November 2019) - Sanz-Cobena, Alberto; Misselbrook, Tom H.; Hernáiz, Pedro; Vallejo, Antonio
Abstract: Ammonia emission from fertilized cropping systems is an important concern for stakeholders, particularly in regions with high livestock densities producing large amounts of manure. Application of pig slurries can result in very large losses of N through NH3 volatilization, thus decreasing the N use efficiency (NUE) of the applied manure. Shallow incorporation has been shown to significantly abate these losses. In this field study, we assessed the impact of contrasting weather conditions on the effectiveness of shallow injection to abate NH3 emissions from pig slurry application to a Mediterranean soil. As potential trade-offs of NH3 abatement, greenhouse gas emissions were also measured under conditions of high soil moisture. Compared with surface application of slurry, shallow injection effectively and significantly decreased NH3 losses independently of weather conditions, but reductions of NH3 emission were greater after heavy rainfall. In contrast, under these conditions, shallow injection triggered higher emissions of N2 O and CH4 . Our findings reinforce the idea that any single-pollutant abatement strategy needs to be designed and assessed in a regional context and considering potential trade-offs in the form of other pollutants. Highlights: Field measurement of NH3 fluxes was performed with a micrometeorological technique. Shallow injection of slurry effectively abated NH3 comparing to surface application. There was a strong impact of rainfall on the NH3 abating effectiveness of injection. Trade-offs (i.e. GHG emissions) were enhanced by shallow injection of pig slurry.